Experimental Standards in Sustainability Transitions: Insights from the Building Sector - Lara Anne Hale (Copenhagen Business School (CBS), 2017)
In this thesis I address how experimental standards are used in the new governance paradigm to further sustainability transitions. Focusing on the case of the Active House standard in the building sector, I investigate experimental standards in three research papers examining the following dynamics: (1) the relationship between commensuration and legitimacy in the formulation and diffusion of a standard's specifications; (2) the role of awareness in standardizing green default rules to establish sustainable consumption in buildings; and (3) the significance of focus on humans in the development of technological standards for sustainable building. Launching from a critical realist social ontology, I collected ethnographic data on the Active House Alliance, its cofounder VELUX, and three of their demonstration building projects in Austria, Germany, and Belgium over the course of three years from 2013 to 2016. In light of the literature on standards and global experimental governance (GXG), I explicate how experiments unfold processually and how standards makers adjust the standard's development to learnings and social insights from these experiments
hdl:10398/9475
Keywords: 650